A DESMUSICALIZAÇÃO DA MÍDIA EM TEMPOS DE HIPERMIDIATIZAÇÃO DA MÚSICA: o empobrecimento estético da música popular na programação televisiva brasileira - Souza, Kleber Mazziero de (2014)
The paper approaches the aesthetic-discursive impoverishment of massive popular song in Brazilian television media, comparing the historical-media-musical context of the 1960s and 1970s and the context of the first half of the second decade of this century. To delimit the discursive impoverishment was defined the concept of unmusicalization of television media. This work, of theoretical nature, aims to point out that the television media has a key role and important part of the responsibility for the impoverishment of discourse in the construction of Brazilian popular music. To do so, first, by analyzing poetic-aesthetic structural elements of musical and literary language of a popular song, was delimited the kind of structured musical work with poetic concern, that imparts an aesthetic standard of excellence. These songs were offered by the Television in the 60s and 70s, today no more. Afterwards, through research literature, documentary and empirical, describes analytical and interpretative way the historical period in which occurred the unmusicalization of television media. Finally, it is concluded that from the popularization of the Internet and the proliferation of various media that allow the access, storage, sharing musical repertoires and, above all, the listening on the move, the mass popular brazilian song, composed with concern poetic no more be longer present in Television and went on to appear in several other media. This broad presence of music in digital media was defined by the concept of hyper-mediatization of music, that would be a component of the unmusicalization of television media